Exome Sequencing Identifies Autosomal-Dominant SRP72 Mutations Associated with Familial Aplasia and Myelodysplasia - Kirwan, Michael (Elsevier, 2012)
Aplastic anemia (AA) and myelodysplasia (MDS) are forms of bone marrow failure that are often part of the same progressive underlying disorder. While most cases are simplex and idiopathic, some show a clear pattern of inheritance; therefore, elucidating the underlying genetic cause could lead to a greater understanding of this spectrum of disorders. We used a combination of exome sequencing and SNP haplotype analysis to identify causative mutations in a family with a history of autosomal-dominant AA/MDS. We identified a heterozygous mutation in SRP72, a component of the signal recognition particle (SRP) that is responsible for the translocation of nascent membrane-bound and excreted proteins to the endoplasmic reticulum. A subsequent screen revealed another autosomal-dominant family with an inherited heterozygous SRP72 mutation. Transfection of these sequences into mammalian cells suggested that these proteins localize incorrectly within the cell. Furthermore, coimmunoprecipitation of epitope-tagged SRP72 indicated that the essential RNA component of the SRP did not fully associate with one of the SRP72 variants. These results suggest that inherited mutations in a component of the SRP have a role in the pathophysiology of AA/MDS, identifying a third pathway for developing these disorders alongside transcription factor and telomerase mutations.